ASPECTS OF THE GERMAN LANGUAGE RELATED TO OTHER SUBJECTS - Bisenbaeva is the daughter of Nargiza Aytbay (Journal of new century innovations, 2023)
Abstract: In order to facilitate the learning of the German language, students' attention should be focused on finding similarities and differences between English and German. The competence of teaching foreign languages forms the student's ability to apply the knowledge, skills and qualifications acquired in a foreign language in everyday life, in a specific field.